Design and Performance Analysis of an Automatic Plastic Mulch Cutting and Punching Machine Using PID Control - Dian Neipa Purnamasari; Achmad Fiqhi Ibadillah; Achmad Ubaidillah; Adi Kurniawan Saputro; Deni Tri Laksono (Jurusan Teknik Elektro Universitas Trunojoyo Madura, 2026)
Plastic mulch is widely used in horticulture to improve soil moisture retention, regulate temperature, and suppress weed growth. However, manual cutting and hole-punching processes are time-consuming, labor-intensive, and produce inconsistent results. This study presents the design and performance analysis of an automatic plastic mulch cutting and punching machine using a PID (Proportional–Integral–Derivative) control system. The system is based on an Arduino Nano. It integrates a DC motor for mulch feeding, a NEMA 17 stepper motor for the punching mechanism, a heater band controlled by an AC dimmer, and a photoelectric sensor for length feedback. PID parameters were initially determined using the Ziegler–Nichols method (Kp=13.5, Ki=2.8, Kd=7.1) and optimized experimentally to Kp=10, Ki=2, and Kd=1. Experimental results show that the optimized PID controller achieves a stable motor response with no oscillation and minimal overshoot, enabling accurate stopping at the desired set point. The system produces a consistent hole spacing of approximately 43.96 cm. Minor deviations were caused by sensor noise and environmental interference.